Case Dismissal on Public Interest Grounds in Criminal Offenses Involving Medical-Use Cannabis - Septiawan Ridho Permadi; Milda Istiqomah; Fachrizal Afandi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
The authority of the Attorney General to dismiss cases (seponeering) under Article 35 paragraph (1) letter c of Law Number 11 of 2021 represents the application of the opportunity principle in prosecution for the sake of public interest. The development of international research and policies, including the 2020 WHO recommendation concerning the medical and economic potential of cannabis, has created an urgent need to reform law enforcement policies regarding narcotic crimes involving cannabis for medical purposes. This study aims to assess the implementation of the opportunity principle in the context of protecting the public interest in the right to health as guaranteed under Articles 28A and 28H of the 1945 Constitution. The research employs a normative legal method with statutory and conceptual approaches by analyzing prosecutorial regulations, narcotics law, and doctrines of public interest and social justice. The findings indicate that the opportunity principle is a fundamental principle in controlling prosecution that must prioritize public benefit, non-discrimination, and the protection of citizens' constitutional rights. The application of seponeering in cases involving medical cannabis is justified as long as it is grounded in public health benefits, economic potential, and the broader interests of society. This study recommends the establishment of transparent prosecutorial guidelines in assessing public interest, enhanced inter-agency coordination in medical cannabis research, and harmonization of narcotics policies to ensure that the implementation of the opportunity principle is not influenced by political interests but truly serves as an instrument of social justice.